Analisis Perilaku Konsumen untuk Implementasi Marketing Mix pada Produk High dan Low Involvement: Consumer Behavior Analysis for Marketing Mix Implementation on High and Low Involvement Products - Alami, Fathoni Nur (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research analyzes consumer behavior in implementing marketing mix on products with high and low levels of involvement. This study aims to understand the differences in consumer behavior patterns towards the two types of products and how marketing mix elements—product, price, place, and promotion—influence purchasing decisions. Through a qualitative approach with in-depth interviews and surveys, it was found that consumers of high involvement products consider quality and brand image factors more, while consumers of low involvement products are more influenced by price and availability factors. The results of this research provide strategic guidance for marketers in designing effective marketing programs according to the type of product and characteristics of targeted consumers.